Terms of Reference: Summaries of Learning on CGIAR’s Ways of Working - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
This Terms of Reference (ToR) presents the approach to compiling evaluative evidence and learning related to five of CGIAR’s seven Ways of Working (WoWs) (2030 Research and Innovation Strategy). The WoWs summaries align with the System Council-endorsed Multi-Year Evaluation Plan (MYEP) contained in the consolidated 2025-27 Workplan for CGIAR's Independent Advisory and Evaluation Service (IAES) (SC/M21/DP5). In 2024, leveraging richness of evaluative data from Science Group (SG) evaluations [portal], IAES advanced a study that summarizes partnership-related evidence (specifically WoW 7 and partially WoW 3), available separately (report). Therefore, this ToR focuses on the remaining five WoWs (see Table 1). 1 The objective of the WoWs summaries is to compile evaluative evidence and learning not only from the past System Council-commissioned evaluations organized by the IAES Evaluation Function (EF) and associated syntheses, but also from other sources, such as the advice and reviews by the Independent Science for Development Council (ISDC); the impact and reach studies of the Standing Panel on Impact Assessment (SPIA); the advisory and audit engagements of CGIAR Internal Audit; as well as Integrated Partnership Board and CGIAR center-led evaluations and studies. A focused literature review will enrich the summaries. Guided by the CGIAR-wide Evaluation Framework and Policy, this effort aims to steer and provide evidence based guidance to inform strategic decisions of the System Council (SC), and its Strategic Impact Monitoring and Evaluation Committee (SIMEC), and CGIAR boards and leadership more broadly, on the implementation and future planning of WoWs. The summaries will assess challenges and identify areas for improvement in implementing CGIAR’s 2030 Research and Innovation Strategy, through the lens of the WoWs. Findings will help CGIAR establish a baseline status of the current state of WoWs and recommend pathways for progress. This will complement the midline independent evaluations of CGIAR programs (2027). The summaries, along with knowledge-sharing activities (e.g., dissemination, briefs, and thematic webinars), will support discussions on CGIAR’s WoWs in the current context, and they will also aid in monitoring the implementation of recommendations from previous independent evaluations and reviews pertaining to these areas. This effort will strengthen linkages between Monitoring, Evaluation, Learning, Impact Assessment, and Foresight (MELIA-F)—an approach that aligns with CGIAR’s institutional efforts to strengthen linkages between functions across centers, programs, and other independent data provider levels, as well as ongoing efforts across CGIAR assurance providers to leverage evidence and advice while reducing assurance fatigue. 2 This ToR is organized into five parts: 1) Purpose and objectives providing the approach for conducting the evaluative evidence and learning of WoWs; 2) Background detailing CGIAR’s strategic direction to work differently, including summary descriptions of each WoW and corresponding summary questions to guide the process; 3) Timeline, milestones, knowledge management and dissemination indicating the timeline for the project, the key deliverables and milestones; 4) Roles and responsibilities in carrying out the evaluation, and summaries including roles of CGIAR’s management, IAES and external consultants; 5) Annex with descriptions for each WoW and the implementation elements as envisaged in the research and innovation strategy, preliminary desk review and mapping of the instances where different WoW topics overlap.